Forecasting Demand for Office Spaces in Ikeja, Nigeria - Olalekan, Oni Taiwo; Oyewole, Bello Musi; Olawande, Oni Ayotunde (Mediterranean Journal of Social Sciences, 2012)
This study was undertaken to analyze the demand for office spaces in Ikeja, Nigeria with a view to determining modelsuseful for forecasting the demand. In attaining the stated aim and objectives of the study, one hypothesis that â€œthere is nosignificant relationship between rental values and demand for officeâ€ was tested. Data were collected from the primary andsecondary sources. Primary sources were data on demand, supply, and rental values of office spaces over a five-year periodobtained through questionnaires administered on one hundred estate surveyors randomly selected in the study. StatgraphicCentrion XV statistical software was used to analyze the data and determine the relationship between the rental value anddemand for office spaces in the study area at 95% confidence level. The study found that there was statistically significantrelationship between the variables P-value = 0.0207, and R2 statistic indicates that the model as fitted explains 87.0188% of thevariability in Average Rental Value; while the correlation coefficient of 0.932839 indicates a relatively strong relationship betweenthe variables. In addition, it was found that demand for banking spaces would continue to decrease whereas purpose-built andconverted office spaces would attract increasing demand from year to year.